O ultrassom pulsado de baixa intensidade na regenera????o do m??sculo tibial anterior de rato: an??lise morfol??gica, organiza????o e deposi????o de col??geno e express??o de fatores regulat??rios miog??nicos - Ribeiro, Jacira Souza (2015)
The low-intensity pulsed ultrasound (LIPUS) has been used to promote muscle repair with better quality and in shorter time, however, there is no standardization for the parameters used in clinical practice. Thus, the aim of this study was to evaluate the effect of USPBI on the repair of skeletal muscle of rats after cryoinjury. Male Wistar rats (n=45) were divided into 3 groups: control; only injury; Injured and treated with LIPUS. The LIPUS application was performed daily, using the stationary mode, pulse 1: 4, 1 MHz frequency, intensity 0.4 W / cm2 for 3 minutes. The injured groups were euthanized at 1, 2, 3 and 7 days following injury induction. The tibialis anterior muscle (TA) was removed for morphological analysis and collagen remodeling, and the muscle sections stained with H&E and Picrosirus Red, respectively. Then, the slides were photographed and quantified using the program "Image J". The analysis of MyoD and myogenin gene expression was performed using real time PCR. The results showed that the USPBI promoted modulation of inflammatory responses with a decrease of inflammatory infiltrates after 1, 2, 3 and 7 days, and reduction of myonecrosis after 7 days, followed by an increase in the number of immature fibers after 3 and 7 days, and increase of blood vessels on days 2, 3 and 7 days. Regarding the deposition of collagen, the results showed better organization of the fibers in all experimental periods, and increased deposition of collagen fibers in the injured group and treated after 2 and 3 days. In addition, treatment with LIPUS promoted increased gene expression of MyoD reduction after 3 days and after 7 days. Regarding myogenin expression, the treated group showed increased expression after 7 days. In conclusion, the LIPUS induced positive effects on muscle repair process leading to reduced inflammation and myonecrosis, increased in the immature fibers and mature blood vessels, as well as modulation of Myod and miogenin in different periods.